ANDROGEN RECEPTOR EXPRESSION IN BREAST CANCER (International Association of Biologicals and Computational Digest, 2022)
Background: Breast cancer is a heterogeneous disease. Accumulating evidence suggests a role for androgen signaling in breast cancer. Androgen receptor (AR) is often expressed in breast cancer and several studies suggest that its role depends on the tumor microenvironment as well as the relative levels of circulating estrogens and androgens. Therefore, the aim is to evaluate role of AR in fourmolecular subtypes of breast cancer.Methods: AR expression was studied on tumor tissues by immunohistochemistry in 125 breast cancer patients and correlated with established clinicopathological parameters and disease status. The SPSSversion 20 for statistical analysis of the data.Results: In this study, nuclear AR expression was seen in 34% of the breast cancer patients. AR expression was seen significantly higher in stage III patients (P=0.05) and low BR tumors (P=0.003). With regards to disease status, patients who undergo disease remission had significant higher AR expression (38%) than patients who developed disease metastases (14%, P=0.03). In Kaplan and Meiersurvival analysis, patients with AR expression had better disease free- (P=0.02) and overall survival (P=0.01). In relation to molecular subtypes, AR expression was seen higher in Luminal A subtype (64%) and Luminal B subtype (52%) as compared to Her-2 subtype (16%) and TNBC subtype (18%, P=0.0001).Conclusion: AR expressing breast cancer can be benefited with AR inhibitors.Key Message: AR is an emerging new therapeutic target in breast cancer. AR expressing breast cancer have improved disease free- and overall survival and can be benefited with AR inhibitors such as bicalutamide, enzalutamide, and apalutamide.
Keywords: androgen receptor, immunohistochemistry, molecular subtypes, breast cancer